Advanced Knitting Technology - Maity, Subhankar; Rana, Sohel; Pandit, Pintu; Singha, Kunal (Woodhead Publishing, 2021)
Advanced Knitting Technology provides complete coverage of the latest innovations and developments in knitting technology, including emerging methods as well as the latest best practice for classical processes. Many technologies can be used for the production of cloth such as weaving, knitting, nonwoven, and braiding. Knitting methods are being selected for a growing range of applications due to the spectacular properties of knitted fabric, such as softer tactile quality, higher stretchability, bulkiness, and functional properties that compare favorably with other woven fabrics. Beyond the well-known apparel applications, specially designed knitted structures are uniquely suitable for high performance applications like reinforcement for composites, medical implants, and geotextiles. This book presents recent advances in knitting technology, including structures, properties and applications of knitted fabrics in modern apparel, activewear, composites, medical textiles, and geotextiles. With reference to the latest industry practice, testing, quality and process control methods for knitting technologies are discussed. Advanced Knitting Technology covers recent advances in knitting technology, properties and performance of knitted structures, their applications in apparel and technical fields.